2018
DOI: 10.3390/molecules23071834
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Metabonomics of Type 2 Diabetes Mellitus

Abstract: With the improvement of living standards and a change in lifestyle, the incidence of type 2 diabetes mellitus (T2DM) is increasing. Its etiology is too complex to be completely understand yet. Metabonomics techniques are used to study the changes of metabolites and metabolic pathways before and after the onset of diabetes and make it more possible to further understand the pathogenesis of T2DM and improve its prediction, early diagnosis, and treatment. In this review, we summarized the metabonomics study of T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 91 publications
(114 reference statements)
2
34
0
Order By: Relevance
“…A large number of metabolomics studies have been conducted in patients with T2DM [24][25][26][27][28] . Metabolomics analysis has, however, not been widely used to identify altered metabolism in healthy people who are at risk for T2DM 6,29 .…”
Section: Discussionmentioning
confidence: 99%
“…A large number of metabolomics studies have been conducted in patients with T2DM [24][25][26][27][28] . Metabolomics analysis has, however, not been widely used to identify altered metabolism in healthy people who are at risk for T2DM 6,29 .…”
Section: Discussionmentioning
confidence: 99%
“…While T1D develops as a consequence of an auto-immune reaction against beta-cells, common causes for T2D are aging and obesity. Obesity causes hyperglycemia, elevated levels of free fatty acids, hypoxia, oxidative stress and an imbalance in many other metabolites, hormones and cytokines ( 123 126 ). This causes a switch in the composition and phenotype of immune cells in metabolic tissues from an anti-inflammatory to a more pro-inflammatory profile and thereby induces chronic low-grade inflammation, which ultimately drives insulin resistance ( 127 129 ).…”
Section: Effects Of the Metabolic Environment On Dcs In Diabetesmentioning
confidence: 99%
“…Polyunsaturated FAs (PUFAs) often have anti-inflammatory effects while many saturated fatty acids (SFAs) serve as pro-inflammatory molecules ( 140 , 141 ). Examples of the latter are palmitic acid (PA) and stearic acid (SA), which together with unsaturated oleic acid (OA) are among the most abundant dysregulated FFAs in obese and T2D patients ( 123 , 142 ). Especially PA is known for its pro-inflammatory effects and detrimental role in T2D pathogenesis ( 143 ).…”
Section: Effects Of the Metabolic Environment On Dcs In Diabetesmentioning
confidence: 99%
“…T2D is a multi‐systemic metabolic disorder, of heterogeneous aetiology, involving biological, genetic and environmental factors 18 . Likewise, recent evidence has suggested that disturbances in the composition of the gut microbiota due to the exposure to high‐fat diets may cause of low‐grade systemic inflammation that may predispose to obesity, metabolic disorders and T2D 19 .…”
Section: Introductionmentioning
confidence: 99%